(untitled) (Journal of Engineering, 2025)
Earth dams in regions with moderate to high seismic activity are crucial for protecting downstream communities. Iraq and its neighboring areas have seen recurrent seismic activity, notably the 2017 Halabja Earthquake, which potentially compromised the integrity of the existing earth dam. The Darbandikhan Dam, affected by an earthquake, has inadequacies in its crest and downstream slope, presenting a greater danger of significant earthquake-induced damage compared to cyclic shocks. Consequently, evaluating the dam’s safety is essential for safeguarding downstream residents and identifying optimal ways to avert slope stability failure amid recurrent seismic activity. Iraq’s seismicity map is being updated to reflect earthquake magnitude, highlighting the need for immediate action. Stone columns are a ground improvement technique that utilizes compacted stone columns to enhance soil strength by increasing shear strength and reducing excess pore water pressure in non-cohesive soils. The behavior of prop stone columns on slopes under static and dynamic loads has not been extensively investigated. This study the influence of stone columns on the stability of the downstream slope of the Al-Adhaim Earth Dam in Diyala Governorate, Iraq, under static and dynamic loads induced by four earthquakes with a peak ground acceleration of 0.2 g for durations of 15 and 30 seconds, using Geo Studio software for various scenarios. The findings indicated that the stone column resulted in a very slight improvement in the safety factor of the downstream slope under static load conditions. The presence of the stone column significantlymproved the safety factor during all seismic occurrences relative to its absence.